1995
DOI: 10.1111/j.1365-2133.1995.tb08684.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed hypersensitivity to one low-molecular-weight heparin with tolerance of other low-molecular-weight heparins

Abstract: We report a patient who developed infiltrated plaques at the sites of subcutaneous injection of a low-molecular-weight heparin. Skin tests and a lymphocyte transformation test revealed hypersensitivity to sandoparin and heparin sodium. The low-molecular-weight heparins nadroparin and dalteparin were subsequently tolerated without adverse effects. Possible risk factors for sensitization are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 11 publications
3
28
0
1
Order By: Relevance
“…This response has been reported to be low and this has been attributed to the self-immunosuppressive characteristic of heparins. 20,21 However, in our study we observed a specific proliferative response by using both monocytes and B cells (the classical LTT) and imDC as APC in six of seven patients evaluated. This indicates that lymphocytes from patients with DTH responded specifically to heparin, but more efficiently when DC were used, as we have previously found with amoxicillin.…”
Section: Discussionmentioning
confidence: 90%
“…This response has been reported to be low and this has been attributed to the self-immunosuppressive characteristic of heparins. 20,21 However, in our study we observed a specific proliferative response by using both monocytes and B cells (the classical LTT) and imDC as APC in six of seven patients evaluated. This indicates that lymphocytes from patients with DTH responded specifically to heparin, but more efficiently when DC were used, as we have previously found with amoxicillin.…”
Section: Discussionmentioning
confidence: 90%
“…Delayed hypersensitivity reactions occur after sensitization to heparin of approximately 2 weeks, but they have been observed after long periods of treatment (Bircher et al, 1995;Boehncke et al, 1996). Most reactions present with erythema at the sites of administration and can range from mild to papulovesicular erythematous plaques (Schindewolf et al, 2010a).…”
Section: F Adverse Reactionsmentioning
confidence: 99%
“…Several types if immunologically mediated reactions to heparins are known: heparin‐associated thrombocytopenia II (HAT II); immediate hypersensitivity reactions such as urticaria, asthma, and anaphylaxis; 8 generalized exanthema; 10 and a delayed‐type hypersensitivity (DTH) reaction 3,4,11,12 . DTH reactions to heparins seem to be underreported since only about 70 cases are described in the literature 13,14 .…”
mentioning
confidence: 99%